Clinical, radiographic, and survivorship analysis of a modular fluted tapered stem in revision hip arthroplasty - Celso Hermínio Ferraz Picado; Aniello Savarese; Vitor dos Santos Cardamoni; Arthur Tomotaka Sugo; Flávio Luís Garcia (Journal of Orthopaedic Surgery, 2019)
Purpose: Modular fluted tapered stems are one of the most commonly used implants in femoral revision surgery. Due to the relative lack of studies on the Restoration modular fluted tapered stem, we conducted a study to evaluate its short- to mid-term clinical, radiographic, and survival outcomes. Methods: We identified all 45 patients treated with this revision stem at our institution. Five patients did not complete the minimum 2-year follow-up, leaving 40 patients (41 hips) for assessment. Mean follow-up was 5.1 years (range 2–11 years). Clinical outcomes were assessed using the Harris hip score (HHS). Radiographs were evaluated for subsidence and loosening. Kaplan–Meier survival analysis was performed using revision of the stem for any reason as end point. Results: The mean HHS improved from 44.6 points preoperatively to 78.4 points at the most recent follow-up ( p < 0.0001). Nonprogressive subsidence occurred in 83% of the hips (mean 2.8 mm; range 1–7 mm). One stem (2.4%) showed progressive subsidence (20 mm) and was considered loose. The most common cause for reoperation was dislocation (three hips, 7.3%). The 10-year survivorship with revision of the stem for any reason as the end point was 93.5% (95% CI, 84.9–100%). Conclusion: There was a significant improvement in the HHS and a low likelihood of revision at short- to mid-term follow-up, adding to the current evidence base for use of this implant in revision surgery. A longer follow-up and a larger number of cases are necessary to fully evaluate its role and performance.